Diagnosis dan Tatalaksana Psoriasis - Muhammad Rafi Eka Putra; Dwi Indria Anggraini; Syahrul Hamidi Nasution; Hendra Tarigan Sibero (CV. Jasa Sukses Abadi, 2023)
Psoriasis is a chronic skin inflammation characterized by clear erythematous plaques, rough scales, and layered silvery white plaques, especially on the elbows, knees, scalp, back, umbilicus, and lumbar region. 125 million people worldwide have psoriasis, with prevalence varying in different countries. Psoriasis has a prevalence of 1% to 3% in Europe and the United States. Psoriasis is a disease caused by an autoimmune condition. The diagnosis of psoriasis can be made based on the clinical picture. The physical examination should include examination of the primary lesion and other common areas affected by psoriasis including the scalp. A family history should be asked to support the diagnosis. The diagnosis can also be established by the presence of candle drip phenomenon, auspitz and kobner (isomorphic) which are symptoms of psoriasis. In addition, a histopathological examination can also be performed with a picture of hyperkeratosis, parakeratosis, acanthosis, Munro's abscess, papillomatosis and vasodilatation subepidermis. Psoriasis therapy is given topically in mild degrees and systemic therapy and phototherapy are given in moderate to severe psoriasis. Topical therapy that can be given is corticosteroids, vitamin D analogues, retinoids, TAR (LCD 3-10%), keratolytics (salicylic acid), and emollients. Systemic therapy used in moderate to severe cases includes acitretin, methotrexate, cyclosporin. Commonly used autotherapy in the treatment of psoriasis are narrowband ultraviolet B (NB-UVB), broadband ultraviolet B (BB-UVB), and topical 8-methoxypsoralen and UVA (PUVA).